A Rare Case of Congenital Rhabdomyosarcoma with Review of the Literature. (20th November 2013) - Singh, Gautam Bir; Arora, Rubeena; Kumar, Deepak; Jain, Manjula; Puri, Vandana
Abstract : We present a rare case of rhabdomyosarcoma of lip in a neonate with multiple lesions within the head and necksub site hitherto unreported in the medical literature. This case report also reviews the scant medical literature on neonatal rhabdomyosarcoma.